Prospective multicenter study of ultrasound‐based measurements of fetal head station and position throughout labor. (November 2015) - Vitner, D.; Paltieli, Y.; Haberman, S.; Gonen, R.; Ville, Y.; Nizard, J.
ABSTRACT: Objectives: To assess the relationship between fetal head position and head station during labor, as measured using an ultrasound‐based system, and the occurrence of occiput posterior (OP) position at delivery. Methods: This was an international prospective observational study including women who delivered between January 2009 and September 2013 in four centers: one in Brooklyn, NY, USA; one in Haifa, Israel; and two in Paris, France. We used an ultrasound‐based system (LaborPro) to monitor fetal head station and position non‐invasively throughout labor. We collected data on demographics, labor parameters and outcome. Results: A total of 595 women were included. In 563 (94.6%) women, fetal head position at delivery was occiput anterior (OA), in 31 (5.2%) it was OP and in one (0.2%) it was occiput transverse. In 89% of pregnancies with intrapartum OP when fetal head station was above −2, the head position turned to OA at delivery; the equivalent figures were 74% and 63% OA at delivery when intrapartum OP was diagnosed at head stations of −2 to < 0, and 0 and below, respectively. Cesarean delivery was performed in 35% of pregnancies with fetal head in OP position at delivery, as opposed to 10% of those with non‐OP position at delivery. On retrospective analysis, all deliveries in OP were already in OP at station −2 and below. Conclusions: In this first assessment of fetal head position at delivery according to fetal head position at various station levels, our data show that 100% of OP positions at delivery were already in OP position at station −2 and below. We did not observe rotation from a non‐OP to an OP position from station −2 and below. Nearly two‐thirds of fetuses in OP at station 0 and below will rotate to an OA position for delivery. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.